The Transformation of the Pope: The Agony and The Ecstasy (1965) and The Second Vatican Council (1962-65) - DeSilva, Jennifer Mara (The journal of religion and film, 2012)
In 1965 the film The Agony and The Ecstasy (dir. Carol Reed) presented Renaissance artistic culture, Catholic iconography, and the papal court in Rome to a popular, broad, and non-denominational audience. Based on the novel by Irving Stone (1961), the narrative follows Michelangelo and Pope Julius II through the decoration of the Sistine chapel ceiling (1508-12), outlining a relationship between the two protagonists that suggests some spiritual equality. In the same way that the Second Vatican Council (1962-65) strove for spiritual renewal and an emphasis on the wonder of humankind’s relationship with God, The Agony and The Ecstasy portrays the Sistine chapel ceiling as a non-denominational emblem of hope that had the power to transform even the pope. The transformation of Pope Julius from an institutionally focused authoritarian into a more humble and spiritual man coincided with the North American media’s embrace of Pope John XXIII and Paul VI’s more ecumenical overtones.